2016
DOI: 10.1002/smr.1830
|View full text |Cite
|
Sign up to set email alerts
|

A method of requirements elicitation and analysis for Global Software Development

Abstract: To perform requirements elicitation and analysis, effective communication and collaboration between stakeholders are necessary. Global Software Development (GSD), where software teams are located in different parts of the world, has become increasingly popular. However, geographical distance, cultural diversity, differences in time zones, and language barriers create difficulties for GSD stakeholders in engaging in effective communication. Taking into consideration the factors involved in GSD, previous researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Ali and Lai [23] addressed the importance of communication and collaboration between stakeholders in the Global Software Development (GSD) context. We found that stakeholders in this context are comparable to stakeholders in eLS context, they are diverse in cultures, geographically dispersed, and there are times zones and language barriers, which made difficulties in engaging into an effective communication.…”
Section: A Requirements Elicitation For Elsmentioning
confidence: 99%
“…Ali and Lai [23] addressed the importance of communication and collaboration between stakeholders in the Global Software Development (GSD) context. We found that stakeholders in this context are comparable to stakeholders in eLS context, they are diverse in cultures, geographically dispersed, and there are times zones and language barriers, which made difficulties in engaging into an effective communication.…”
Section: A Requirements Elicitation For Elsmentioning
confidence: 99%
“…Thus, the requirement analysis method that helps to bridge the communication gap between a customer and a developer is offered in paper [4]. The method for analyzing requirements for software development, proposed in [6], is based on the joint participation of representatives of IT-project stakeholders. However, the results presented in [7] show that such methods can be improved by structuring the perception of the system created by the participants of an IT-project as a formal conceptual mental model.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Thus, paper [9] proposed to reduce the number of errors in requirements by establishing a special method of requirements analysis that helps bridge the gap in communication between a customer and a developer. Article [10] suggests a method for identifying and analyzing requirements to software development, based on the joint participation of representatives of all stakeholders in the IT project.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%